FUNDRAISING DAN EFEKTIVITAS PENTONG KOIN TERHADAP SOSIAL EKONOMI ERA DISRUPSI KECAMATAN TUREN - Mohammad Dullah; Zaenullah Zaenullah (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2022)
The aims of this study to: 1) find out the Pentong Coin Fundraising and the Impact on Earnings, 2) the Management (LAZISNU) in Turen District. 3) The effectiveness of the management of NU Coin Fund on the Socio-Economic Society of the Era Disruption. This research use a qualitative method. The results are as follows: 1) The concept of Infak through the NU Coin Movement, can be said as a brilliant and tactical step in implementing the I'anah Syahriyyah Concept. 2) Fundraising on the Pentong Coin activity is not intentional or organized, this is an activity that has long been done by scholars in order to all of the jam'iyyah are obedient to the religion and carry out Islamic syarai'at properly and correctly and of course this is will have a positive impact on increasing pentong coins in Turen District. 3) the management of LAZISNU is in accordance with the management concept, 4) the management of the NU Pentong Coin has been effective and does require an in-depth study so that pentasarrufan becomes more useful, especially in the Disruption Era (covid-19 pandemic).